2017
DOI: 10.3892/mmr.2017.7275
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-136-5p in hepatocellular carcinoma and its clinicopathological significance

Abstract: The clinical significance of microRNA (miR)-136-5p in hepatocellular carcinoma (HCC) has not been verified. Therefore, in the current study, the authors aimed to explore miR-136-5p expression and its clinical significance in HCC, as well as to investigate its potential target genes function. The authors detected the levels of miR-136-5p in 101 pairs of HCC and para-cancer tissues via reverse transcription-quantitative polymerase chain reaction. Gene Expression Omnibus database and the Cancer Genome Atlas (TCGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Additionally, in the context of colorectal cancer, it was discovered that the elevated lncRNA LEF1-AS1 expression has correlated to shorter periods of overall survival and recurrence-free survival of patients (Chen, Yu, Xu, & Shen, 2017). As a predicted downstream miR according to bioinformatics analysis, miR-136-5p shows therapeutic significance in HCC by functioning as a tumor suppressor through a variety of pathways, yet the detailed regulatory mechanism still awaits further investigation (Ding et al, 2017). Besides, miR-136-5p interacts with lncRNA CRNDE to potentiate the glioma malignancy via B-cell lymphoma-2 and Wnt2 (Li et al, 2017).…”
mentioning
confidence: 99%
“…Additionally, in the context of colorectal cancer, it was discovered that the elevated lncRNA LEF1-AS1 expression has correlated to shorter periods of overall survival and recurrence-free survival of patients (Chen, Yu, Xu, & Shen, 2017). As a predicted downstream miR according to bioinformatics analysis, miR-136-5p shows therapeutic significance in HCC by functioning as a tumor suppressor through a variety of pathways, yet the detailed regulatory mechanism still awaits further investigation (Ding et al, 2017). Besides, miR-136-5p interacts with lncRNA CRNDE to potentiate the glioma malignancy via B-cell lymphoma-2 and Wnt2 (Li et al, 2017).…”
mentioning
confidence: 99%
“…MiR-136 was initially identified by cloning studies in mouse, and later verified in human embryonic stem cells [38]. Researches have shown that miR-136 acts as an anti-carcinoma miRNA in lung [39] and hepatocellular carcinoma [40], and involves the metastasis of colon cancer by suppressing epithelial-to-mesenchymal transition [41]. Here, we showed that both the cellular and exosomal level of miR-136 were higher in UMSCs than in OMSCs.…”
Section: Discussionmentioning
confidence: 57%
“…MiR-136 was initially identified by cloning studies in mouse, and later verified in human embryonic stem cells [34]. Researches shown that miR136 acts as an anti-carcinoma miRNA in lung [35] and hepatocellular carcinoma [36], and involves the metastasis of colon cancer by suppressing epithelialto-mesenchymal transition [37]. Here, we showed that both cellular and exosomal level of miR-136 were higher in UMSCs than in OMSCs.…”
Section: Discussionmentioning
confidence: 57%